The survivors of low class contractor in construction industry related government contract with specific at Kelantan - Abd Rahim, Ibrahim (2012)
Class F contractors are the most number of contractors all among contractors' classes in Malaysia. The presence of many contractors gives effect to the government. The total number of Class F contractors nationwide stood at 29, 349 while the company from only the state of Kelantan are 2,296. Many Class F contractors rely on contracts issued by the government alone and not interested in getting the project issued by the private sector. This study evaluates the level of Class F contractors' dependence on government contracts. T he data were collected by conducting document study with Pusat Khidmat Kontraktor (PKK), various government departments, that involved directly in connection with the granting of government contracts to contractors Class F. Also, 40 set of questionnaire were distributed among the Class F contractors in Kelantan. The results show that the main reason of Class F contractor more interested in government project rather than private sector is due to the thoroughness of the private sector in choosing a qualified contractor to perform the contract, with 4.03 Average Index Value (PT). The main problem faced by Class F contractor is the intense competition in getting contract as there are so many Class F contractors in the market. Among the measures to minimize on government contracts are ensuring 10% allocation in the Class A Contractors is distributed to Class F Contractors, limit of licence contract and urge the government to issue the annual Class F grant.